Combination and inducible adjuvants targeting nucleic acid sensors. (August 2018) - Temizoz, Burcu; Kuroda, Etsushi; Ishii, Ken J
Abstract : Innate immune sensing of nucleic acids derived from invading pathogens or tumor cells via pattern recognition receptors is crucial for mounting protective immune responses against infectious disease and cancer. Recently, discovery of tremendous amounts of nucleic acid sensors as well as identification of natural and synthetic ligands for these receptors revealed the potential of adjuvants targeting nucleic acid sensing pathways for designing efficacious vaccines. Especially, current data indicated that unique adjuvants targeting TLR9 and stimulator of interferon genes (STING)-dependent cytosolic nucleic acid sensing pathways along with the combinations of already existing adjuvants are promising candidates for this purpose. Here, we review current vaccine adjuvants targeting nucleic acid sensors and their modes of action.